Membranous Nephropathy (MN) Recurrence After Renal Transplantation - Passerini, Patrizia; Malvica, Silvia; Tripodi, Federica; Cerutti, Roberta; Messa, Piergiorgio (Frontiers in Immunology, 2019)
Primary membranous nephropathy (MN) is a frequent cause of NS in adults. In native kidneys the disease may progress to ESRD in the long term, in some 40- 50% of untreated patients. The identification of the pathogenic role of anti-podocyte autoantibodies and the development of new therapeutic options has achieved an amelioration in the prognosis of this disease. MN may also develop in renal allograft as a recurrent or a de novo disease. The true incidence of the recurrent form is difficult to assess. This is mainly due to the variable graft biopsy policies in kidney transplantation, among the different transplant centers. Anti-phospholipase A2 receptor (PLA2R) autoantibodies are detected in 70-80% of patients. The knowledge of anti-PLA2R status before transplant is useful in predicting the risk of recurrence. In addition, the serial survey of the anti-PLA2R titers is important to assess the rate of disease progression and the response to treatment. Currently, there are no established guidelines for prevention and treatment of recurrent MN. Symptomatic therapy may help to reduce the signs and symptoms related to the nephrotic syndrome. Anecdotal cases of response to cyclical therapy with steroids and cyclophosphamide have been published. Promising results have been reported with rituximab in both prophylaxis and treatment of recurrence. However, these results are based on observational data, and prospective controlled trials are still missing. De novo MN affects about 2% of renal allograft patients and usually develop later than recurrence. De novo MN differs from recurrent MN in pathogenesis and morphologic features. Any form of renal damage causing exposition of normally hidden epitopes resulting in an autoantibody response, can cause a de novo MN. In this regard anti-PLA2R level is useful being always negative in de novo MN. Renal biopsy remains the golden standard for diagnosis. In immunofluorescence specimens, IgG1 deposition dominates in patients with de novo MN while IgG4 dominates in primary as well as in recurrent MN.